2012
DOI: 10.1155/2012/147520
|View full text |Cite
|
Sign up to set email alerts
|

A Nonparametric Shewhart-Type Quality Control Chart for Monitoring Broad Changes in a Process Distribution

Abstract: This paper develops a distribution-free (or nonparametric) Shewhart-type statistical quality control chart for detecting a broad change in the probability distribution of a process. The proposed chart is designed for grouped observations, and it requires the availability of a reference (or training) sample of observations taken when the process was operating in-control. The charting statistic is a modified version of the two-sample Kolmogorov-Smirnov test statistic that allows the exact calculation of the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…"Quality control is a procedure or set of procedures intended to ensure that a manufactured product or performed service adheres to a defined set of quality criteria or meets the re-Manuscript received January 25, 2020. ; accepted April 11,2020. Vesna Jevremović, Atif Avdović are with the State University of Novi Pazar, Department of Mathematical Sciences, Novi Pazar, Serbia quirements of the client or customer" [5].…”
Section: Quality Control Principles and Methodsmentioning
confidence: 99%
“…"Quality control is a procedure or set of procedures intended to ensure that a manufactured product or performed service adheres to a defined set of quality criteria or meets the re-Manuscript received January 25, 2020. ; accepted April 11,2020. Vesna Jevremović, Atif Avdović are with the State University of Novi Pazar, Department of Mathematical Sciences, Novi Pazar, Serbia quirements of the client or customer" [5].…”
Section: Quality Control Principles and Methodsmentioning
confidence: 99%
“…Bakir 31 pointed out that "Realistically, however, when a special cause influences a process, it may cause a shift in more than one parameter (location, scale, skewness, etc.) of the process distribution".…”
Section: Designing Of Proposed Control Chartmentioning
confidence: 99%
“…A normal distribution of the data is a pre-requisite of statistical process control and the calculation of process capability indices to more accurately estimate process capability over time (Montgomery, 2004). Bakir (2012) reported that a normal distribution is desirable for performing process capability analysis and for such analysis to be representative. Further information on studies of normality associated with the use of statistical process control can be found in Chakraborti (2006) and Zhou and Tsung (2010).…”
Section: Descriptive Statistics Parametersmentioning
confidence: 99%